2021
DOI: 10.1051/parasite/2020075
|View full text |Cite
|
Sign up to set email alerts
|

Molecular prevalence, characterization and associated risk factors of Anaplasma spp. and Theileria spp. in small ruminants in Northern Pakistan

Abstract: This study was conducted in four districts (Malakand, Swat, Bajaur and Shangla) of Northern Pakistan to investigate the prevalence, associated risk factors and phylogenetic analyses of Theileria and Anaplasma species in small ruminants. A total of 800 blood samples, 200 from each district, were collected from apparently healthy animals. PCR assays were performed using generic primers for Anaplasma spp. and Theileria spp. as well as species specific primers for A. ovis and T. ovis. Overall infection prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 48 publications
6
16
3
Order By: Relevance
“…The The results of the phylogenetic tree of the local sequences of T. ovis was showed that it possesses common phylogenetic characteristics and a high evolutionary relationship with the sequences of T. ovis recorded in the NCBI GenBank for different countries including Pakistan and India, with the 100% Identity, after performing 100 nucleotide sequence reconstructing using Bootstrap analysis (Abid et al, 2021;Eliwa et al, 2021;Niaz et al, 2021). In addition, results of the phylogenetic tree of the local sequences of T. lestoquardi was also showed that it possesses common phylogenetic characteristics and a high evolutionary relationship with the sequences of T. lestoquardi recorded in the NCBI GenBank.…”
Section: Discussinmentioning
confidence: 99%
See 1 more Smart Citation
“…The The results of the phylogenetic tree of the local sequences of T. ovis was showed that it possesses common phylogenetic characteristics and a high evolutionary relationship with the sequences of T. ovis recorded in the NCBI GenBank for different countries including Pakistan and India, with the 100% Identity, after performing 100 nucleotide sequence reconstructing using Bootstrap analysis (Abid et al, 2021;Eliwa et al, 2021;Niaz et al, 2021). In addition, results of the phylogenetic tree of the local sequences of T. lestoquardi was also showed that it possesses common phylogenetic characteristics and a high evolutionary relationship with the sequences of T. lestoquardi recorded in the NCBI GenBank.…”
Section: Discussinmentioning
confidence: 99%
“…Ovine theileriosis (OT) is a worldwide distribution disease with highly morbidity and mortality rates, in spite of availability treatment and conducting tick control programs (Ozubek et al, 2017). It is mainly caused by Theileria lestoquardi, previously called (T. hirci) and Theileria ovis previously called (T. recondita) (Niaz et al, 2021;Qi et al, 2018), which were biologically transmitted by hard ticks belonging to the Ixodidae family and the most common genus's are Haylomma, Rhipicephalus, Boophilus, Haemaphysalis and Amblyomma (M'ghirbi et al, 2013;Gebrekidan et al, 2014;Rjeibi et al, 2016;Mamatha et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Species of Theileria (T.) that infect bovines are T. annulata, T. orientalis, T. velifera, T. parva, T. mutans, T. taruortargi, T. sinesis, and new species T. yokoyama which is closely related to T. annulata (Bishop et al 2004;Cao et al 2013;Anupama et al 2015;Hasan et al 2017;Ola-Fadunsin et al 2017;Sivakumar et al 2019;Niaz et al 2021). Prevalence of Theileria species is also reported in disease-endemic areas of Pakistan and is mostly found in the bovine population where it is transmitted by Hyalomma anatolicum and its prevalence is reported by different researchers in different areas of the country ( Durrani and Kamal 2008;Durrani et al 2010;Khattak et al 2012;Khan et al 2013;Jabbar et al 2015;Farooqi et al 2017;Ali et al 2019;Zeb et al 2019;Zeb et al 2020;Parveen et al 2021).…”
Section: Theileria Species Causing Infection In Animalsmentioning
confidence: 99%
“…Tick-borne haemoparasitic protozoa, Piroplasms are classified into genera Theileria (T.) and Babesia (B.). Piroplasmosis is also known as the cause of Texas fever, which is an endemic disease of domestic animals in tropical, temperate, and subtropical areas of the world (Niu et al 2012;Aydin et al 2015;Siddique et al 2020;Niaz et al 2021). These parasites belong to phylum Apicomplexa, family Theileriidae and Babesiidae.…”
Section: Introductionmentioning
confidence: 99%
“…Genus Theileria possesses certain unique characteristics which differentiate its species from other apicomplexan parasites e.g., they do not reside in the parasitophorous vacuoles in comparison to Toxoplasma and Plasmodium, are nonmotile and lack apical complex (Bishop et al 2004;von Schubert et al 2010). Theileria species, causing infection in livestock population include: T. annulate, T. parva, T. ovis, T. lestoquardi, T. separate, T. mutans, T. velifera, and T. recondite (Zaeemi et al 2011;Kumsa et al 2013;Li et al 2014;Aydin et al 2015;Guo et al 2018;Remesar et al 2019;Niaz et al 2021;Roy et al 2021). Theileria species are different from Babesia sp.…”
Section: Introductionmentioning
confidence: 99%